2012
DOI: 10.1111/j.1471-0528.2012.03311.x
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of circulating placental growth factor, vascular endothelial growth factor, soluble fms‐like tyrosine kinase 1 and soluble endoglin in the prediction of pre‐eclampsia: a systematic review and meta‐analysis

Abstract: Background Biomarkers have been proposed for identification of women at increased risk of developing pre-eclampsia.Objectives To investigate the capacity of circulating placental growth factor (PlGF), vascular endothelial growth factor (VEGF), soluble fms-like tyrosine kinase-1 (sFLT1) and soluble endoglin (sENG) to predict pre-eclampsia.Search strategy Medline and Embase through October 2010 and reference lists of reviews, without constraints.Selection criteria We included original publications on testing of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
148
2
7

Year Published

2012
2012
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 231 publications
(172 citation statements)
references
References 70 publications
9
148
2
7
Order By: Relevance
“…[43][44][45] Although sEng values alone or in combination with other pro-and antiangiogenic factors are significantly altered in PE serum, it has proven to be a poor biomarker of the disorder. 46 Cell-free fetal DNA cfDNA and cffDNA are also probable combined biomarkers of PE, mainly due to their sensitivity and specificity in biological fluids. 47,48 The identification of the methylated RASSF1A promoter gene, which is elevated in early-PE pregnancies, [49][50][51] offers a promising alternative to the quantification of cffDNA, using Y-chromosome-specific sequences.…”
mentioning
confidence: 99%
“…[43][44][45] Although sEng values alone or in combination with other pro-and antiangiogenic factors are significantly altered in PE serum, it has proven to be a poor biomarker of the disorder. 46 Cell-free fetal DNA cfDNA and cffDNA are also probable combined biomarkers of PE, mainly due to their sensitivity and specificity in biological fluids. 47,48 The identification of the methylated RASSF1A promoter gene, which is elevated in early-PE pregnancies, [49][50][51] offers a promising alternative to the quantification of cffDNA, using Y-chromosome-specific sequences.…”
mentioning
confidence: 99%
“…Unfortunately, the markers so far investigated do not appear to have a high enough positive predictive value to use routinely in clinical practice [28]. A recent systematic review investigated levels of circulating PlGF, VEGF, sFlt1 and sEng in the serum and plasma of pregnant women prior to 30 weeks' gestation, but before clinical onset of pre-eclampsia [29]. Modest rises in PlGF, sFlt1 and sEng concentrations were all noted prior to 30 weeks' gestation in women who developed pre-eclampsia, but test accuracies for these markers remained too poor for accurate prediction of pre-eclampsia in clinical practice [29].…”
Section: Renalmentioning
confidence: 99%
“…A recent systematic review investigated levels of circulating PlGF, VEGF, sFlt1 and sEng in the serum and plasma of pregnant women prior to 30 weeks' gestation, but before clinical onset of pre-eclampsia [29]. Modest rises in PlGF, sFlt1 and sEng concentrations were all noted prior to 30 weeks' gestation in women who developed pre-eclampsia, but test accuracies for these markers remained too poor for accurate prediction of pre-eclampsia in clinical practice [29]. The use of first or second trimester maternal uterine artery Doppler velocimetry has been extensively investigated both in isolation and in combination with routinely measured first trimester serum markers (e.g., b-hCG, PAPP-A, inhibin A and activin A) and maternal risk factor assessment [30].…”
Section: Renalmentioning
confidence: 99%
“…However, a recent systematic review that synthesized results of 34 studies calculated summary diagnostic odds ratios of PlGF 9.0 (95% CI 5.6-14.5), sFlt-1 6.6 (95% CI 3.1-13.7), and sEng 4.2 (95% CI 2.4-7.2), which correspond to sensitivities of 32%, 26%, and 18%, respectively. The authors concluded that the test accuracies of all four markers might be too poor for accurate prediction of preeclampsia in clinical practice [44]. To date, however, the antiangiogenic factor assays have been used to discriminate preeclampsia from other etiologies of renal compromise, and have proven useful in a variety of select clinical scenarios, including presumed glomerulonephritis [45], lupus [46], and in patients on hemodialysis [47].…”
Section: Diagnosismentioning
confidence: 99%